Bronchioalveolar stem cells derived from mouse-induced pluripotent stem cells promote airway epithelium regeneration - Kawakita, Naoya (Stem Cell Res Ther, 2020)
BACKGROUND: Bronchioalveolar stem cells (BASCs) located at the bronchioalveolar-duct junction (BADJ) are stem cells residing in alveoli and terminal bronchioles that can self-renew and differentiate into alveolar type (AT)-1 cells, AT-2 cells, club cells, and ciliated cells. Following terminal-bronchiole injury, BASCs increase in number and promote repair. However, whether BASCs can be differentiated from mouse-induced pluripotent stem cells (iPSCs) remains unreported, and the therapeutic potential of such cells is unclear. We therefore sought to differentiate BASCs from iPSCs and examine their potential for use in the treatment of epithelial injury in terminal bronchioles. METHODS: BASCs were induced using a modified protocol for differentiating mouse iPSCs into AT-2 cells. Differentiated iPSCs were intratracheally transplanted into naphthalene-treated mice. The engraftment of BASCs into the BADJ and their subsequent ability to promote repair of injury to the airway epithelium were evaluated. RESULTS: Flow cytometric analysis revealed that BASCs represented ~ 7% of the cells obtained. Additionally, ultrastructural analysis of these iPSC-derived BASCs via transmission electron microscopy showed that the cells containing secretory granules harboured microvilli, as well as small and immature lamellar body-like structures. When the differentiated iPSCs were intratracheally transplanted in naphthalene-induced airway epithelium injury, transplanted BASCs were found to be engrafted in the BADJ epithelium and alveolar spaces for 14 days after transplantation and to maintain the BASC phenotype. Notably, repair of the terminal-bronchiole epithelium was markedly promoted after transplantation of the differentiated iPSCs. CONCLUSIONS: Mouse iPSCs could be differentiated in vitro into cells that display a similar phenotype to BASCs. Given that the differentiated iPSCs promoted epithelial repair in the mouse model of naphthalene-induced airway epithelium injury, this method may serve as a basis for the development of treatments for terminal-bronchiole/alveolar-region disorders.